Developments in enzyme and microalgae based biotechniques to remediate micropollutants from aqueous systems—A review. Issue 10 (25th March 2022) - Usmani, Zeba; Sharma, Minaxi; Lukk, Tiit; Karpichev, Yevgen; Thakur, Vijay Kumar; Kumar, Vivek; Allaoui, Abdelmounaaim; Awasthi, Abhishek Kumar; Gupta, Vijai Kumar
Abstract: While the production and usage of pesticides, pharmaceuticals, and personal care products have greatly improved the quality of life for humans, their application has increasingly been contaminating aqueous systems with micropollutants due to seepage, run-off, effluent discharge and uptake in the environment. Micropollutants exhibit considerable ecotoxicities and adverse effects on human health, making them a critical environmental concern. Current micropollutant remediation methods which involve advanced oxidation processes and membrane technologies are costly, consume excess chemicals, require high amounts of energy, form harmful by-products and sludge that are difficult to manage. The usage of oxidative laccases and peroxidases, microalgae and microalgae-bacteria consortia are emerging as novel green alternatives for the remediation of micropollutants from contaminated aqueous systems. This review details recent advances made in the application of green media utilized in micropollutant remediation through degradation, immobilization, adsorption, bioaccumulation and co-metabolism. These methods are discussed as secondary treatment techniques for wastewater plant effluents or as a tertiary treatment in conjunction with other chemical and biological technologies to metabolize toxic chemicals in-situ and yield innocuous outputs. A critical discussion on advantages, application, current developments, drawbacks and future perspectives of these biotechniques is presented. Graphical Abstract: UF0001